Investigation of the trust status of the nurse–patient relationship - Ozaras, Gözde; Abaan, Süheyla (2018)
Background:Professional nurses provide holistic healthcare to people and deal with patients closely. Furthermore, patients need nurses to do self-care and patients trust them for their treatments. Therefore, trust is extremely important in a professional care relationship and in satisfactory patient outcomes.Objective:The aim of this study was to examine the patients’ views on the trust status toward nurses and the factors important for the development of trust in a nurse–patient relationship.Research design:This research was planned as a descriptive cross-sectional study.Participants and research context:The study was carried out between April and July 2014 at the oncology hospital of a university in Ankara, Turkey. The sample size was calculated by power analysis and was composed of 356 inpatients diagnosed with cancer. For data collection, a questionnaire and the “Trust in Nurses Scale” were used.From the hospital and written informed consent obtained from participating patients:Approval from the University Clinical Research Ethics Committee was obtained. Written approval was obtained from the hospital and consent letter from the patients.Findings:The average score on the scale was 24.5 ± 3.9, meaning that patients had a high level of trust toward nurses in this hospital. The patients who were in the 50–59 age group and men had statistically higher scores compared with other groups. Patients’ answers revealed that themes of “Personal and Professional Characteristics” were important when developing trust, however “Mistreatment, Professional Incapability, and Communication Problem” were important causing mistrust toward the nurses.Conclusion:In this study, the nurses’ professional competencies and interpersonal caring attributes emerged as most important in developing trust. This study paid attention to the values and attitudes that develop patients’ trust toward nurses. Moreover, the findings raise ethical questions about how the patients’ basic rights are to be protected and how their trust level can be heightened. Nurse managers need to assess continuously how trust toward nurses is developed, protected, and maintained in their institutions.
Keywords: Trust; Patients; oncology hospital; Nursing; nurse–patient relationship